Age estimation from clavicle by histomorphometry method: a review - Pasuk Mahakkanukrauh,; Inthasan C, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Histomorphometry method, the quantitative study of histology, is a useful method to estimate age of death in the present and ancient skeletal remains by measurable morphology of osteon. This method, which reduces individual bias and difference in the level of experience for estimation of age, is useful for constructing paleodemographic models and forensic identifications when adult fragmentary skeletal remains are encountered. Most parts of skeletons that are studied by histomorphometry method are femur, tibia, rib, and clavicle. Clavicle bone has been poorly studied except for Caucasian populations. Moreover, clavicle is a very interesting bone because it is a non-weight bearing bone, is usually found as entire bone and has different bone development from other long bones. Thus, the interest of this review article is on the age estimation by histomorphometry method of clavicle. This review article also describes the histomorphometry method, clavicle bone, bone remodeling, and forensic application of clavicle with histomorphometry method.